Pengaruh Penerapan Model Discovery Learning dengan Media Realia Terhadap Motivasi Belajar dan Penguasaan Pengetahuan Faktual dan Konseptual IPA Siswa Kelas IV - Fenny Aptensi; Irwan Koto (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2023)
This research aims to determine the effect of implementing the discovery learning model with realia media on learning motivation and mastery of factual and conceptual science knowledge in class IV students. This type of research is quantitative research. The research method used was a quasi experiment using the matched only pretest-posttest control group design. The population of this study were all fourth grade students at SDN 86 Bengkulu City. The sample in this study was 22 students from class IVA as the experimental class, and 22 students from class IVB as the control class. Sampling used total sampling technique. The instrument used is a multiple choice written test sheet consisting of factual and conceptual knowledge dimensions with a total of 20 questions and a learning motivation questionnaire sheet with a total of 20 statement items given in the pretest (before learning takes place) and posttest (after learning takes place). Research data was analyzed using inferential analysis, namely the t-test. Based on the research results, it shows that there is an influence of applying the discovery learning model with realia media on learning motivation and mastery of factual and conceptual science knowledge in class IV students.